2018
DOI: 10.1177/0255761418796864
|View full text |Cite
|
Sign up to set email alerts
|

Psychological benefits of networking technologies in children’s experience of ensemble music making

Abstract: Little is currently known about the possible benefits of using networked technology to enhance ensemble performance. This study explored whether the introduction of specially devised technology-networked tablets using traditional music notation-to a primary school orchestra would enhance the experience of ensemble music. Particular emphasis was placed on how the technology could help children to overcome practical problems associated with ensemble playing for early-stage musicians (e.g., keeping in sync with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
12
0
3
Order By: Relevance
“…At best the PD process creates rich epistemic artefacts that 'solve' the initial problem. Our formal (Hanrahan et al 2018) and informal observations and testimonials suggest that Syncphonia indeed succeeds in enhancing access to and experience of notation-based ensemble performance. PD is also a form of tacit research process that deepens our knowledge of the area, and it these surfacing the insights that is the focus of this paper.…”
Section: Participatory Design: Co-constructing Epistemic Artefactsmentioning
confidence: 63%
See 1 more Smart Citation
“…At best the PD process creates rich epistemic artefacts that 'solve' the initial problem. Our formal (Hanrahan et al 2018) and informal observations and testimonials suggest that Syncphonia indeed succeeds in enhancing access to and experience of notation-based ensemble performance. PD is also a form of tacit research process that deepens our knowledge of the area, and it these surfacing the insights that is the focus of this paper.…”
Section: Participatory Design: Co-constructing Epistemic Artefactsmentioning
confidence: 63%
“…As such, it has required new approaches in design methodology and research methodology During our first funded research period, in which we worked with a study group of school children aged 9-11. A thematic analysis (Hanrahan et al 2018) revealed that participants felt an enhanced sense of enjoyment and belonging; they also reported feeling an enhanced better 'sound' due to stress reduction and the ability to read longer and more complex pieces, leading syncphonia JMTE paper rev 2 to an enhanced sense of the structure and flow of the music (Hanrahan et al 2018). Since the first trial, the usage of the App has broadened considerably beyond primary schools and continues to grow.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen (2015) adopted mobile devices with an application Auralbook to assist young learners in learning aural skills, indicating that the method not only significantly improved students' learning achievement but also positively impacted their motivation to learn music. Hanrahan et al (2019) integrated networked tablets into primary school ensemble music practicing, and found that the technology did help promote early-stage young music learners' learning enjoyment and motivation. In addition to assisting learners in learning music through the features of mobile devices, the integration of effective learning strategies can also be considered to enhance students' motivation and music learning effectiveness.…”
Section: Keyword Analysismentioning
confidence: 99%
“…This implies that students have fewer opportunities to receive comments from others or to compare their own performance with that of others. With the help of computer and network technologies, learners are able to compare their own performance with that of others, and to receive instant feedback from others via network communications, implying more opportunities to think in depth and to make reflections (Hanrahan et al, 2019;Williams, 2014). Several studies have further indicated that integrating technology into music education not only enhances students' performance (Chen et al, 2020), but also improves their attitudes towards learning music (Ho, 2004), their interest in learning music (Kim, 2013), and their learning engagement in music classes (Crow, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology in music education increases the performance (Byrne & MacDonald, 2002), participation (Crow, 2006), interest (Comber et al, 1993;Savage, 2007), and motivations (Ho, 2004;Kim, 2013;Savage, 2007) of students, as well as their musical perceptions (Kim, 2013). Furthermore, it contributes to their musical creativity (Addessi & Pachet, 2005;Savage, 2005) and functions by improving their psychological states (Hanrahan, Hughes, Banerjee, Eldridge & Kiefer, 2019). Additionally, using technology in music education makes it possible for children to relate more closely to school music and facilitates students' creation of connections between the music they listen to and their real lives (Cain, 2004).…”
Section: Introductionmentioning
confidence: 99%